SOCIOLOGICAL STUDY IN THE SCRIPTURE "LOVE THERE ARE OTHER PEOPLE" THE WORKS OF UTUY TATAN SONTANI - Neng Elis Handayani; Gina Amelia Pitri; Dwi Rinna Artiani; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Apart from being a means of entertainment, drama can also be used as a means of learning and as an object of research. The object of study in this research is a drama script by Tatang Sontani entitled "Unfortunately There Are Other People". from the sociological study of literature in the script "Unfortunately There Are Others" by Utuy Tatang Sontani focusing on the analysis of the moral values contained in the drama. This research uses a literary sociology approach to understand how the drama reflects social reality and moral values related to human life. The research results show that the drama "Love There Are Others" expresses various forms of moral values related to human relationships in the social environment of society. This is shown through interactions between characters. This research also shows that the drama can be used as an alternative teaching material in language and literature education in high schools.